PENERAPAN STRATEGI BAURAN PEMASARAN PADA PRODUK OLAHAN KACANG METE SEBAGAI UPAYA MENINGKATKAN DAYA TARIK WISATA DI DESA MEDANA - Susilawati Susilawati; I Putu Gede; Syech Idrus (Journal Of Responsible Tourism, 2023)
The marketing of cashew nuts in Medana village has not yet expanded, which is only marketed in North Lombok Regency and even then not entirely by using only word of mouth promotional media. This research was conducted to support tourism activities, especially the seventh Sapta Pesona, namely memories by making cashew nuts as souvenirs. This study aims to describe the steps for developing the marketing of processed cashew nuts using the 7p marketing mix. This study uses a qualitative descriptive method, where researchers collect data through interviews, observation, and documentation. The analysis technique used is data reduction, data presentation, and drawing conclusions. From the results of the research carried out, it was found that the steps for developing the marketing of cashew products as souvenirs for tourism were the development and improvement in terms of products, prices, places, promotions, people/HR, processes, and physical evidence in order to attract interest. local tourists and foreign tourists